QUALITY ENHANCHEMENT (TECHNICAL AND ECONOMICAL ASPECT) FOR POST-HARVEST PERISHABLE COMMODITIES WITH INDIRECT SOLAR DRYING SYSTEM - Farahdiansari, Ardana Putri; Stighfarrinata, Rizky (LPPM Universitas Jambi, 2026)
This study evaluated the performance of a closed solar drying system for perishable horticultural commodities, with chili (Capsicum frutescens) as the case study, considering both technical and economic aspects. Drying experiments were conducted in Tuban Regency, Indonesia, using 20 kg of fresh chili divided into two samples, dried for 12 hours to achieve a final moisture content of 15%. Technical performance was assessed by measuring moisture content reduction, drying rate, and Specific Energy Consumption (SEC), which was found to be 4.0 kWh/kg, indicating efficient energy use. Economically, the total daily production cost for 20 kg of fresh chili yielding 3 kg of dried chili was calculated at IDR 260,000, resulting in a unit cost of IDR 86,700/kg. Dried chili could be marketed at IDR 88,000–95,000/kg, providing potential daily profit and reducing postharvest losses. In comparison, selling fresh chili during peak harvest at reduced market prices (IDR 12,650/kg) with 15-30% spoilage resulted in a unit cost of IDR 16,579/kg and exposed farmers to financial losses. These results demonstrate that indirect solar drying not only improves product quality and energy efficiency but also serves as a viable postharvest strategy to mitigate economic risk, stabilize income, and add value for small- and medium-scale chili farmer.